(untitled) (Social Science Review, 2023)
This article concerns ethnicity and identity politics in Chittagong Hill Tracts of Bangladesh. This article used the power relation approach of Foucault, Althusser, and Mills, Barth’s idea of ethnicity and boundary maintenance, primordial and instrumentalist approaches to ethnicity, and primordial and socia-constructionist approaches to identity. The politics of identity formation and movements of Bangalee, Chakma, and Tripura ethnic communities are associated with multidimensional issues. Some of these are - collectiveness, struggle for existence, ensuring rights, protecting traditions, and securing land and natural resources of the hills. The study used qualitative data collection methods such as observation and participation, key informant interviews, life history, case studies, and narratives. Data analysis followed the qualitative technique by interpreting various aspects or layers of meaning and relationships among ethnic communities. The findings further show that Chakma and Tripura communities bear a nationalist and political ideology through the term Jumma, while Bangalees have a reconstructed image of the hill Bangalee. This article, thus, critically examines the politics of identity formation in CHTs, focusing on inter-ethnic relations of power and political practices. Social Science Review, Vol. 39(2), June 2022 [Special Issue] Page 1-17